3D Interconnected Mesoporous Alumina with Loaded Hemoglobin as a Highly Active Electrochemical Biosensor for H2O2. Issue 11 (27th March 2018) - Yang, Xuanyu; Cheng, Xiaowei; Song, Hongyuan; Ma, Junhao; Pan, Panpan; Elzatahry, Ahmed A.; Su, Jiacan; Deng, Yonghui
Abstract: Alumina is one of the most common and stable metal oxides in nature, which has been developed as a novel adsorbent in enrichment of biomolecules due to its excellent affinity to phosphor or amino groups. In this study, ordered mesoporous alumina (OMA) with interconnected mesopores and surface acidic property is synthesized through a solvent evaporation induced co‐assembly process using poly(ethylene oxide)‐ b ‐polystyrene (PEO‐ b ‐PS) diblock copolymer as a template and aluminium acetylacetonate (Al(acac)3 ) as the aluminium source. The pore size (12.1–19.7 nm), pore window size (3.5–9.0 nm) and surface acidity (0.092–0.165 mmol g −1 ) can be precisely adjusted. The highly porous structure endows the OMA materials with high hemoglobin (Hb) immobilization capacity (170 mg g −1 ). The obtained Hb@OMA composite is used as an electrocatalyst of biosensor for convienet and fast detection of hydrogen peroxide (H2 O2 ) with a low H2 O2 detection limit of 1.7 × 10 −8 m and a wide linear range of 2.5 × 10 −8 to 5.0 × 10 −5 m . Moreover, the Hb@OMA sensors show a good performance in real time detection of H2 O2 released from Homo sapiens bone osteosarcoma, indicating their potential application in complex biological processes. Abstract : Ordered mesoporous alumina with 3‐D interconnected large pores, tunable pore window size and high surface Lewis activity was rationally synthesized through a facile soft templating method. Electrochemical biosensor based on the obtained ordered mesoporous alumina with immobilized hemoglobin is fabricated which show an excellent performance for the electrochemical detection of H2 O2 .